English Language Academic Writing Difficulties Experienced By Yemeni Postgraduate Students At Public Universities In Malaysia - Bahfee, Adel Abood Saeed (2019)
This study investigates academic writing difficulties experienced by Yemeni postgraduate students at public universities in Malaysia. It is a mixed methods study in which both quantitative and qualitative data were collected, analyzed and triangulated. The quantitative data were collected through questionnaires that were completed by 65 Yemeni postgraduate students from five public universities in Malaysia, while qualitative data were collected using focus group interviews. While quantitative data were analyzed using Statistical Package for Social Sciences (SPSS), qualitative data were analyzed through content analysis in which data were transcribed and coded thematically.The current study investigated these academic writing difficulties. The Yemeni postgraduate students were given the opportunity to express their views about these difficulties and the strategies they use to overcome them. The findings of this study also reveal that academic writing at the university level is a higher level with different nature because it includes different genres which may include brief research papers, creative writing, explanation of graphs, brief reports or descriptions of class activities, academic essays, journal writing, brief summary of articles and personal essays.